Analysis of knowledge and attitudes about sexual education in adolescents from the educational institution "Algarrobos" -Piura: Proposal for an educational model 2020 - Preciado-Marchan, Anita (2021)
Introduction: Sex education in adolescents has been and continues to be a concern for the education and health sector, health indicators show every day how early pregnancies, sexually transmitted infections, gender violence and school dropouts increase. Objective: To propose an educational model to strengthen the knowledge and attitudes towards sexual education in Adolescents of the Educational Institution "Algarrobos", Piura 2020. Materials and Methods: Non-experimental, quantitative, descriptive and purposeful design, sample of 95 adolescents from EI "Algarrobos", analyzed V1: Knowledge and attitudes towards sexuality, V2: Sexual education model. Survey technique: Knowledge questionnaire, Likert test and document review, descriptive statistics: SPSS version 25 program, Excel 2018 program. Results: More than 50% of adolescents do not have knowledge of sex education and have unfavorable attitudes. An educational model was developed based on the Professional Biographical Model, the educational guidelines and pedagogical orientations of comprehensive sexuality education (ESI), the proposal for the training of teachers in ESI of Minedu, based on the socio-cognitive theories of Piaget and the theory of Bruner's discovery; model that has its pedagogical, didactic, sociocultural and legal foundations. Conclusions: Students have a need to know fundamental aspects of their sexuality, not only biological, but also affective, social and intercultural. The future dynamic, inclusive and democratic application of this model validated by expert judgments, aims to strengthen this knowledge and attitudes in adolescents.